2021
DOI: 10.21037/apm-20-2526
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for diabetic retinopathy in the communities of Shenzhen

Abstract: Background: To understand the prevalence of diabetic retinopathy (DR) in Shenzhen and to analyze the risk factors for the occurrence and development of DR. Based on the comprehensive information system for diabetes prevention and control in the communities of Shenzhen in 2019, six community health service centers in Shenzhen were used as research sites to carry out multicenter, cross-sectional screening studies.Methods: Cluster random sampling was used to collect data from 904 patients with diabetes in Shenzhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…The present DR prevalence was similar to the prevalence in some population-based studies conducted in Chinese mainland cities such as Liaoning (11.9%) [ 16 ], Weitang (10.38%) [ 17 ], Yangxi (8.19%) [ 18 ], Beijing (8.1%) [ 19 ] and communities in Shanghai (9.4%) [ 20 ]. Interestingly, the present DR prevalence was also lower than that in some other Chinese mainland cities such as Handan (14.24%) [ 21 ], Dongguan (18.2%) [ 22 ], and Shenzhen (18.58%) [ 23 ] and Suzhou (18.0%) [ 24 ]. Different sampling methods and characteristics of the study population may lead to different DR prevalence.…”
Section: Discussioncontrasting
confidence: 61%
“…The present DR prevalence was similar to the prevalence in some population-based studies conducted in Chinese mainland cities such as Liaoning (11.9%) [ 16 ], Weitang (10.38%) [ 17 ], Yangxi (8.19%) [ 18 ], Beijing (8.1%) [ 19 ] and communities in Shanghai (9.4%) [ 20 ]. Interestingly, the present DR prevalence was also lower than that in some other Chinese mainland cities such as Handan (14.24%) [ 21 ], Dongguan (18.2%) [ 22 ], and Shenzhen (18.58%) [ 23 ] and Suzhou (18.0%) [ 24 ]. Different sampling methods and characteristics of the study population may lead to different DR prevalence.…”
Section: Discussioncontrasting
confidence: 61%
“…Yun Peng et al. found that duration, the use of antidiabetic drugs and diabetic peripheral neuropathy were independent risk factors for DR in a Shenzhen community in China ( 30 ). A high WHR is an indicator of abdominal obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the prevalence of DR was 33.5% in the Chinese population [ 24 ]. While, it was 18.58% in another study in china [ 25 ]. However, the prevalence of DR was higher among Saudi Arabia’s population.…”
Section: Discussionmentioning
confidence: 88%